MeerKAT discovery of 13 new pulsars in Omega Centauri. Issue 3 (9th January 2023) - Chen, W; Freire, P C C; Ridolfi, A; Barr, E D; Stappers, B; Kramer, M; Possenti, A; Ransom, S M; Levin, L; Breton, R P; Burgay, M; Camilo, F; et al.
ABSTRACT: The most massive globular cluster in our Galaxy, Omega Centauri, is an interesting target for pulsar searches, because of its multiple stellar populations and the intriguing possibility that it was once the nucleus of a galaxy that was absorbed into the Milky Way. The recent discoveries of pulsars in this globular cluster and their association with known X-ray sources was a hint that, given the large number of known X-ray sources, there is a much larger undiscovered pulsar population. We used the superior sensitivity of the MeerKAT radio telescope to search for pulsars in Omega Centauri. In this paper, we present some of the first results of this survey, including the discovery of 13 new pulsars; the total number of known pulsars in this cluster currently stands at 18. At least half of them are in binary systems and preliminary orbital constraints suggest that most of the binaries have light companions. We also discuss the ratio between isolated and binaries pulsars, and how they were formed in this cluster.